Determined by reasons: a competence account of acting for a normative reason - Mantel, Susanne (Routledge studies in ethics and moral theory, 2018)
Acting for a normative reason -- The casual approach and the role of dispositions -- The normative competence account -- Two ways of acting for a normative reason -- Squaring normative reasons with motivating reasons -- The identity thesis -- Worldly reasons in the deliberative realm -- Worldly reasons in the explanatory realm -- Worldly reasons and the psychological tradition